Feasibility of spectral shaping for detection and quantification of coronary calcifications in ultra-low dose CT - Vonder, Marleen; Meyer, Mathias; Henzler, Thomas (European radiology, 2017)
ObjectivesTo evaluate detectability and quantification of coronary calcifications for CT with a tin filter for spectral shaping.MethodsPhantom inserts with 100 small and 9 large calcifications, and a moving artificial artery with 3 calcifications (speed 0-30 mm/s) were placed in a thorax phantom simulating different patient sizes. The phantom was scanned in high-pitch spiral mode at 100 kVp with tin filter (Sn100 kVp), and at a reference of 120 kVp, with electrocardiographic (ECG) gating. Detectability and quantification of calcifications were analyzed for standard (130 HU) and adapted thresholds.ResultsSn100 kVp yielded lower detectability of calcifications (9 % versus 12 %, p = 0.027) and lower Agatston scores (p < 0.008), irrespective of calcification, patient size and speed. Volume scores of the moving calcifications for Sn100 kVp at speed 10-30 mm/s were lower (p < 0.001), while mass scores were similar (p = 0.131). For Sn100 kVp with adapted threshold of 117 HU, detectability (p = 1.000) and Agatston score (p > 0.206) were similar to 120 kVp. Spectral shaping resulted in median dose reduction of 62.3 % (range 59.0-73.4 %).ConclusionsCoronary calcium scanning with spectral shaping yields lower detectability of calcifications and lower Agatston scores compared to 120 kVp scanning, for which a HU threshold correction should be developed. Key points • Sn100kVp yields lower detectability and lower Agatston scores compared to 120kVp • Adapted HU threshold for Sn100kVp provides Agatston scores comparable to 120kVp • Sn100 kVp considerably reduces dose in calcium scoring versus 120 kVp
Published online: 29 August 2016
Gesehen am 20.07.2018